Nanoindentation response of semiconductors - LeBourhis, E. (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2008)
The paper reviews the nanoindentation behaviour of semiconductors under concentrated load. We consider first, fundamental aspects regarding the mechanical resistance to contact loading of semiconductor single crystals (indentation strain, hardness-yield stress relationship). Then, the paper summarizes recent studies regarding nanoindentation structure and geometrical size effect.